Allelopathy: How Plants Suppress Other Plants - James J. Ferguson; Bala Rathinasabapathi; Carlene A. Chase (EDIS, 2013)
Allelopathy refers to the beneficial or harmful effects of one plant on another plant, both crop and weed species, from the release of biochemicals, known as allelochemicals, from plant parts by leaching, root exudation, volatilization, residue decomposition, and other processes in both natural and agricultural systems. This 5-page fact sheet introduces the concept of allelopathy and mentions potential applications as an alternative weed management strategy. Written by James J. Ferguson, Bala Rathinasabapathi, and Carlene A. Chase, and published by the UF Department of Horticultural Sciences, March 2013.